Stakeholder dynamics in local digital governance: evaluating public complaint system in Pekanbaru, Indonesia - Handrian, Eko; Putera, Roni Ekha; Asrinaldi, Asrinaldi; Zetra, Aidinil (Otoritas : Jurnal Ilmu Pemerintahan, 2025)
This study evaluates stakeholder dynamics in the implementation of Pekan Kita (PEKA), a digital innovation for public complaints in Pekanbaru City, Indonesia. Using a qualitative approach and a modified Stakeholder Salience Model, the research analyzes the interaction between stakeholder attributes power, legitimacy, and urgency and institutional structures affecting the sustainability of digital public innovations. Data were collected through in-depth interviews, observations, and document analysis involving 16 key informants from policy, operational, and community levels. Findings reveal that although several actors possess formal authority and legitimacy, their sense of urgency remains low due to rigid bureaucratic incentives, sectoral egos, and weak cross-agency coordination. Conversely, citizens demonstrate high urgency but lack institutional power and recognition, marginalizing their role in digital governance. The study identifies seven strategic pillars for sustainable innovation: strengthening cross-agency coordination, redesigning bureaucratic incentives, enhancing citizen co-creation, enabling two-way communication, managing inter-actor conflict, building human capacity and infrastructure, and reformulating the role of the ICT agency as an innovation orchestrator. This research contributes to the theoretical development of stakeholder analysis in e-government by revising the classic salience model to include informal power, bureaucratic incentives, and symbolic local political leadership. The proposed model offers a more contextual and dynamic framework for understanding the complexities of digital transformation in developing-country bureaucracies.